A Comparative Study of the Incidence of Hypoglycaemia and Hypocalcaemia in Neonatal Seizures Occurring within 72 Hours of Birth Admitted in NICU at a Tertiary Care Centre - Ur Rahman, Zia; S, Abdul Khaleef; S, Md Sajid Basha; D, Murali Krishnaiah (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Recognition of hypoglycaemia and hypocalcaemia in Neonatal seizures is important for to prompt diagnosis and therapeutic implications. Study aimed to analyse the incidence of hypoglycaemia and hypocalcaemia in neonatal seizures occurring within 72 hours of birth in 32-37 weeks preterm and term (37-42 weeks) babies. Subjects and Method: A prospective hospital based observational study enrolled total of 105 neonates presenting with seizures activity within 72 hours of birth admitted to NICU of SV Medical College, Tirupati from September 2013 to October 2014. Samples selected by Simple random sampling method. Detailed antenatal, natal and postnatal history including CNS examination were taken and investigations estimated includes complete blood counts and picture, random blood sugar, and serum ionic calcium. The analysis data was chi square test with SPSS for Windows (Ver 20), SPSS Inc. New York. Results: The results was In neonatal seizures occurring within 72 hours of birth, hypoglycaemia (62.9%) was common, more so in preterm babies both hypoglycaemia 9 (37.5%) and combination of hypoglycaemia and hypocalcaemia 9 (37.5%). The association between type of delivery and hypoglycaemia/ hypocalcaemia shown significant different (p=0.002). The association between Birth Weight and hypoglycaemia/ hypocalcaemia shown a very high significant different (p< 0.001). Conclusion: In neonatal seizures occurring within 72 hours of birth, hypoglycaemia (62.9%) was common, more so in preterm babies both hypoglycaemia 09 (37.5%) and combination of hypoglycaemia and hypocalcaemia 09 (37.5%).